Hematuria in Patients With Beta-Thalassemia Major (Iranian Journal of Kidney Diseases, 2010)
Introduction. Our information about renal involvement in beta-thalassemia major is limited. Recently, few studies have reported proteinuria, hypercalcuria, phosphaturia, and oversecretion of tubular damage markers; however, hematuria has not yet been meticulously studied in these patients. We investigated hematuria in patients with beta-thalassemia major.Materials and Methods. Urinalysis was performed in 500 patients with beta-thalassemia major under a regular blood transfusion program. In those with hematuria (at least 3 to 5 erythrocytes per high-power field) a second urinalysis was done at the next transfusion time.Results. The patients ranged in age from 6 months to 32 years. The male-female ratio was 1.05:1. Hematuria was detected in 55 (10.6%), including 9.8% of those younger than 20 years and 20.0% of those older than 20 years. Hematuria was persistent in 79.2% of the second urinalyses. Sixty-four percent of the patients with hematuria were females. A blood transfusion program had been started during the first year of life in 81% percent of the patients with hematuria. Sterile pyuria was detected in 4% and proteinuria in 16% of the patients with hematuria, while these figures in patients without hematuria were 2.1% (P = .56) and 1.4% (P = .002), respectively.Conclusions. We found that in patients with beta-thalassemia major, the risk of hematuria rises with age. Moreover, proteinuria seems to be more common in those with hematuria. Further studies are needed to ascertain the importance of these findings.